The Effect of Turkish Teacher Candidates’ Personality Traits on Academic Self-efficacy and Effective Communication Self-efficacy - Erkan Aydın (SAGE Open)
The study aims to uncover the influence of positive personality traits among Turkish language teacher candidates on their effective communication self-efficacy and academic self-efficacy. Furthermore, it seeks to identify the mediating variable effect of effective communication self-efficacy. To achieve these objectives, the research employed the relational survey model. The sample comprised 345 students enrolled in the Turkish Language Teaching Department at various universities in Türkiye at the undergraduate level. Structural equation modeling was utilized for the analysis. The research findings indicate that possessing positive personality traits positively impacts the academic self-efficacy levels of pre-service teachers. Additionally, having positive personality traits contributes to an increase in their effective communication self-efficacy levels. The study demonstrates that as pre-service teachers’ effective communication self-efficacy levels rise, so do their academic self-efficacy levels. In conclusion, the research unveils that the effective communication self-efficacy levels of pre-service teachers mediate the relationship between positive personality traits and academic self-efficacy, and effective communication self-efficacy determines the strength of the connection between these two variables.